NHC-Catalyzed Synthesis of Benzazole-Phosphine Ligands under an Air Atmosphere - Ren, Wei; Zuo, Qian-Ming; Yang, Shang-Dong (Synlett, 2019)
An efficient strategy for the synthesis of benzazole-phosphine ligand precursors via N-heterocyclic carbene catalyzed aerobic oxidative cyclization reaction has been performed. The reaction displays broad functional group tolerance and high atom economy, and the transformation has been further applied to benzazole-phosphine ligand synthesis.
Keywords: N-heterocyclic carbenes; oxidative cyclization; organcocatalysis; benzazoles phosphine ligand